2011
DOI: 10.1152/jn.00164.2011
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hyperpolarization-activated currents in layer 5 pyramidal neurons enhances excitability in focal cortical dysplasia

Abstract: Albertson AJ, Yang J, Hablitz JJ. Decreased hyperpolarizationactivated currents in layer 5 pyramidal neurons enhances excitability in focal cortical dysplasia. J Neurophysiol 106: 2189 -2200, 2011. First published July 27, 2011; doi:10.1152/jn.00164.2011.-Focal cortical dysplasia is associated with the development of seizures in children and is present in up to 40% of intractable childhood epilepsies. Transcortical freeze lesions in newborn rats reproduce many of the anatomical and physiological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 80 publications
3
35
1
Order By: Relevance
“…To determine whether mice expressing mthtt in PV+ neurons exhibit increased movement, we evaluated their ambulatory activity in the open field paradigm. Interestingly, this is one of the few murine models with mthtt overexpression to exhibit overt hyperactivity, as most mouse models of HD typically demonstrate reduced locomotion and impaired coordination (Carter, Lione et al 1999; Gu, Li et al 2005; Hickey, Gallant et al 2005; Albertson, Yang et al 2011). Electrophysiological characterizations revealed a reduced probability of GABA release in the motor cortex as well as an overall reduction in gamma frequency stimulation-evoked GABA release, and we propose that these alterations could enhance cortical output to the spinal cord and/or the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether mice expressing mthtt in PV+ neurons exhibit increased movement, we evaluated their ambulatory activity in the open field paradigm. Interestingly, this is one of the few murine models with mthtt overexpression to exhibit overt hyperactivity, as most mouse models of HD typically demonstrate reduced locomotion and impaired coordination (Carter, Lione et al 1999; Gu, Li et al 2005; Hickey, Gallant et al 2005; Albertson, Yang et al 2011). Electrophysiological characterizations revealed a reduced probability of GABA release in the motor cortex as well as an overall reduction in gamma frequency stimulation-evoked GABA release, and we propose that these alterations could enhance cortical output to the spinal cord and/or the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, HCN channels dampen dendritic excitability in hippocampal cortical neurons and modify overall synaptic integration and somatic-dendritic coupling (Magee, 1999; Poolos et al, 2002; Santoro et al, 2000). Pharmacological blockade of HCN channels causes neuronal and network hyperexcitability (Albertson et al, 2013; 2011). Furthermore, animals lacking Hcn1 have more excitable neurons, are more prone to seizures, and have higher seizure-induced mortality (Huang et al, 2009; Santoro et al, 2010).…”
Section: Intrinsic Plasticitymentioning
confidence: 99%
“…In response to L5 stimulation, evoked epileptiform discharges consisted of a large depolarization with superimposed APs. We have shown that the I h antagonist ZD 7288 reduces I h in L5 pyramidal cells (Albertson et al 2011). In the preset study, we measured the effects of ZD 7288 on input resistance and "sag" responses induced by hyperpolarizing current pulses.…”
Section: H Constraint Of Epileptiform Events In Pyramidal Neuronsmentioning
confidence: 92%
“…Reductions in I h or HCN channels have been reported in pilocarpine (Jung et al 2007), kainate (Shin et al 2008), and kindling (Powell et al 2008) models of epilepsy. Spontaneously epileptic WAG/ Rij rats (Strauss et al 2004) and rats with cortical malformations (Albertson et al 2011) also exhibit changes in I h . Reduced seizure thresholds are seen in HCN1-knockout mice (Huang et al 2009).…”
mentioning
confidence: 99%